The Correlation between the Use of Automated Writing Evaluation and the Level of Writing Anxiety in Argumentative Writing Class (RETAIN, 2022)
This present study aims to explore the level and the types of writing anxiety among the students, along with the use of AWE in argumentative writing class. This study also examined the correlation between the use of Automated Writing Evaluation (AWE) and students’ writing anxiety. The Second Language Writing Anxiety Inventory (SLWAI) and the questionnaire about the use of AWE were employed on 40 students majoring in English Language Education at a university in Surabaya. The result of this study showed that 29 students (72%) at a moderate level of writing anxiety, 8 students (20%) at a low level of writing anxiety, and 3 students (8%) at a high level of writing anxiety. Furthermore, there are 35 students (88%) who have a high level of the use of AWE, 5 students (12%) have a moderate level of the use of AWE, and there are no students who have a low level of the use of AWE. This study also reported there is no correlation between the level of students’ writing anxiety and the use of AWE during argumentative writing class with p-value = 0.136 and r = 0.240. Keywords: Writing Anxiety, Automated Writing Evaluation, Argumentative Writing.